Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/ftd.0000000000000341.
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin Pharmacokinetics and Monitoring in Pediatric Patients with Febrile Neutropenia

Abstract: Based on a log-linear method of analysis, current dosing seems to be consistently producing gentamicin exposure below predefined pharmacokinetic targets, suggesting that an increase in the recommended starting dose of gentamicin may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In this group of patients, children's body composition and the PK of gentamicin are affected by chemotherapy and pathological changes such as presence of fever, decreased muscle mass, increased renal clearance and malnutrition . Both gentamicin Cl and Vd were reported to be increased in paediatric patients with cancer . On the other hand, Llanos‐Paez et al demonstrated that typical gentamicin Cl in oncology patients (0.08 L/h/kg) was lower compared to non‐oncology children of a similar age receiving gentamicin intramuscularly (0.10 L/h/kg).…”
Section: Discussionmentioning
confidence: 99%
“…In this group of patients, children's body composition and the PK of gentamicin are affected by chemotherapy and pathological changes such as presence of fever, decreased muscle mass, increased renal clearance and malnutrition . Both gentamicin Cl and Vd were reported to be increased in paediatric patients with cancer . On the other hand, Llanos‐Paez et al demonstrated that typical gentamicin Cl in oncology patients (0.08 L/h/kg) was lower compared to non‐oncology children of a similar age receiving gentamicin intramuscularly (0.10 L/h/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a 1-compartment model was selected. Also for other aminoglycosides in pediatric neutropenic fever, individual PK calculations using a 1-compartment model have been used [32]. For amikacin, both 1-and 2compartment models have been published in neonates and/or children [7,17].…”
Section: Discussionmentioning
confidence: 99%
“…This limits the exposure of children to gentamicin in cases where an appropriate indication for use is lacking, not only important in reducing unnecessary toxicity associated with the use of gentamicin, but also in reducing the development of antibiotic resistance over the long term. Although there has been considerable improvement in practice following the guideline change, there may continue to be a number of admissions where gentamicin dosage may be suboptimal, potentially contributing to an increased risk of nephrotoxicity and ototoxicity. Results on gentamicin dosing and TDM in this patient cohort have been previously reported .…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been considerable improvement in practice following the guideline change, there may continue to be a number of admissions where gentamicin dosage may be suboptimal, potentially contributing to an increased risk of nephrotoxicity and ototoxicity. Results on gentamicin dosing and TDM in this patient cohort have been previously reported . Information on gentamicin toxicity events such as ototoxicity and nephrotoxicity or the frequency of admissions where piperacillin/tazobactam was in appropriate empiric monotherapy was not collected as part of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation